Industrial Work Readiness of Culinary Students Through Teaching Factory at SMK Negeri 1 Lembah Gumanti - Refi, Febriana; Anggraini, Ezi; Elida, Elida; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Vocational High Schools (SMK) are required to produce graduates who are ready to work and have skills according to industry needs. SMK Negeri 1 Lembah Gumanti is one of the centers of excellence (SMK PK) that focuses on curriculum development and facilitating students with skills to prepare students for the world of work by implementing Teaching Factory learning. This study aims to determine whether there is a positive relationship between the Teaching Factory learning model and the industrial work readiness of culinary students at SMK Negeri 1 Lembah Gumanti using a correlational quantitative approach with a total sampling of 50 respondents. Data collection used two questionnaires, each with 20 statement items with a score of 5 on a Likert scale: the Teaching Factory questionnaire and the student industrial work readiness questionnaire. The data analysis technique used is descriptive analysis that describes the variables of the Teaching Factory learning model and student industrial work readiness, as well as analysis requirements tests, and hypothesis tests. The results of the study indicate that between the Teaching Factory learning model and student industrial work readiness there is a significant positive relationship in the strong category (0.739). TeFa is in the high category (26%), while student industrial work readiness is in the very high category (30%). The correlation coefficient test using the T-test revealed that t-test > t-table (7.600 > 0.279), indicating a positive and significant correlation. A high Teaching Factory score increases students' work readiness.